Evaluation of the cytotoxicity and antibacterial activity of a synthetic tunicamycin derivative against Mycobacterium avium complex - Colombatti Olivieri, Maria A.; Price, Neil P. J.; Jackson, Michael A.; Bannantine, John P. (Frontiers in Microbiology, 2025)
Two synthetic derivatives of the tunicamycin antibiotic, TunR1 and TunR2, were previously developed that significantly reduced toxicity in eukaryotes but remained potent against Gram positive prokaryotes. TunR2 has been demonstrated to be non-toxic and effective in a zebrafish model of mycobacterial infection. In this study, we evaluated the cytotoxicity in bovine cells and the antibacterial effect of natural Tun as well as two synthetic derivatives of Tun, designated TunR1 and TunR2, on Mycobacterium avium complex. The average minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) for TunR2 ranged from 16 to 32 μg/mL when tested on seven Mycobacterium avium subspecies paratuberculosis (Map) strains. MICs were higher for the closely related Mycobacterium avium subspecies hominissuis (>32 μg/mL), and lower for Mycobacterium marinum (0.025 μg/mL) and Mycobacterium smegmatis (3.2 μg/mL). Effects on the Map cell wall could be detected by electron microscopy at TunR2 concentrations above 128 μg/mL. The toxicity of TunR2 in eukaryotes was evaluated in vitro by hemolysis of bovine red blood cells (RBCs) and by MTT viability assay on a bovine epithelial cell line, cultured bovine peripheral blood mononuclear cells (PBMCs), and bovine monocyte-derived macrophages (bMDMs). The concentrations of the drug that produce 50% of inhibition (IC50) in each of these three cell types was lower than the MIC for Map. Hemolytic activity was demonstrated in 91% of RBCs when exposed to 31 μg/mL of TunR2. Also, low-dose TunR2 treatment of infected macrophages did not significantly decrease Map survival after 48 h of infection. These results suggest that TunR2 is not a good candidate to treat Map infections.